Cerebral malaria: gamma-interferon redux - Hunt, Nicholas H.; Ball, Helen J.; Hansen, Anna M.; Khaw, Loke T.; Guo, Jintao; Bakmiwewa, Supun; Mitchell, Andrew J.; Combes, Valéry; Grau, Georges E. R. (Frontiers in Cellular and Infection Microbiology, 2014)
There are two theories that seek to explain the pathogenesis of cerebral malaria, the mechanical obstruction hypothesis and the immunopathology hypothesis. Evidence consistent with both ideas has accumulated from studies of the human disease and experimental models. Thus some combination of these concepts seems necessary to explain the very complex pattern of changes seen in cerebral malaria. The interactions between malaria parasites, erythrocytes, the cerebral microvascular endothelium, brain parenchymal cells, platelets and microparticles need to be considered. One factor that seems able to knit together much of this complexity is the cytokine interferon-gamma. In this review we consider findings from the clinical disease, in vitro models and the murine counterpart of human cerebral malaria in order to evaluate the roles played by interferon-gamma in the pathogenesis of this often fatal and debilitating condition.